2019
DOI: 10.1111/ene.13975
|View full text |Cite
|
Sign up to set email alerts
|

The cerebrospinal fluid CD4/CD8 ratio and interleukin‐6 and ‐10 levels in neurosarcoidosis: a multicenter, pragmatic, comparative study

Abstract: Background and purpose Neurosarcoidosis is a rare inflammatory disorder of unknown cause. The aim of this study was to evaluate the value of T/B lymphocyte population counts and the concentrations of the cytokines interleukin (IL) 6 and IL‐10 in the cerebrospinal fluid (CSF) of neurosarcoidosis patients. Methods A retrospective study CSF biomarkers was conducted in patients with neurosarcoidosis who underwent CSF analysis between 2012 and 2017 as well as various control populations. Results Forty‐three patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…However, its sensitivity is low, ranging from 0 to 66.7% [156,164]. The CD4/CD8 ratio in CSF is higher in neurosarcoidosis than in multiple sclerosis and other neurological inflammatory disorders and may be helpful for the differential diagnosis [165]. Hypoglycorachia (up to 14%) and oligoclonal bands (up to 42%) are also biological features associated with neurosarcoidosis [156].…”
Section: Neurosarcoidosismentioning
confidence: 99%
“…However, its sensitivity is low, ranging from 0 to 66.7% [156,164]. The CD4/CD8 ratio in CSF is higher in neurosarcoidosis than in multiple sclerosis and other neurological inflammatory disorders and may be helpful for the differential diagnosis [165]. Hypoglycorachia (up to 14%) and oligoclonal bands (up to 42%) are also biological features associated with neurosarcoidosis [156].…”
Section: Neurosarcoidosismentioning
confidence: 99%
“…Moreover, an IL-6 level >50 pg/mL predicted progression and shorter relapse-free survival than those with an IL-6 level <50 pg/mL. 66 As part of CSF analysis, IL-6 and CD4/CD8 may increase diagnostic sensitivity and specificity for NS.…”
Section: Diagnostic Approach Neurosarcoidosis Manifestationsmentioning
confidence: 96%
“…Another study reported increased IL-6 levels in the cerebrospinal fluid (CSF) of patients with neurosarcoidosis as compared to patients with multiple sclerosis or other inflammatory disorders. CSF concentration of IL-6 > 50 pg/mL was associated with a higher risk of relapse or progression of neurosarcoidosis (25). Genetic variations in the genes encoding IL-6 were preferentially upregulated in patients with severe and progressive sarcoidosis thus giving further evidence of the pathogenic role of this proinflammatory cytokine (26,27).…”
Section: Interleukin-6 Blockingmentioning
confidence: 98%